Vocal Fold Nodules: Morphological and Immunohistochemical Investigations - Martins, Regina Helena Garcia [UNESP]; Faveri, Julio de [UNESP]; Domingues, Maria Aparecida Custódio [UNESP]; de Albuquerque e Silva, Rafael; Fabro, Alexandre [UNESP] (Mosby-elsevier, 2010)
The objective of this study was to investigate the morphological and immunohistochemical characteristics of vocal fold nodules. The study design was prospective and retrospective. For the histological study, we reviewed 15 slides from the surgical cases of vocal fold nodules, in which we analyzed epithelium, basal membrane (bm), and lamina propria. For the transmission and scanning electron microscopy (TEM, SEM) studies, five new cases on vocal fold nodules were included. Immunohistochemistry study was carried out in the 15 specimens, using antifibronectin, antilaminin, and anticollagen IV antibodies. The main histological alterations were epithelial hyperplasia (73.33%), basement membrane thickening (86.66%), edema, and fibrosis (93.33%). SEM-reduction in mucous lacing and increase in the desquamating cells, without epithelial erosion. TEM-hyperplasia of the epithelium, enlargement of the intercellular junctions, which was filled by fluid, subepithelial thickening of the lamina reticularis, and break points in the basal membrane. Immunohistochemistry-we identified greater immunoexpression of fibronectin on the basal membrane, on the lamina propria, and around the vessels. Antilaminin and anticollagen IV antibodies showed higher pigmentation on the endothelium of the vessels than that on the basal membrane. In vocal fold nodules, combined assessment using light microscopy, electron microscopy, and immunohistochemistry can reveal important morphological details useful in characterizing these lesions.
Keywords: Vocal fold nodules; Morphology; Immunohistochemistry